GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 59 species occurrences available in GBIF matching the query: TaxonKey: Senecio formosoides Cuatrec. Country: Colombia HasCoordinate: true HasGeospatialIssue: false. The dataset includes 59 records from 11 constituent datasets: 1 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 2 records from Colección Herbario Federico Medem Bogotá - FMB. 1 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 6 records from Herbario Pontificia Universidad Javeriana. 25 records from University of Amsterdam (NL) - Páramo Vegetation Research, Chingaza - Cruz Verde - Monserrate -Guasca, Colombia. 6 records from University of Amsterdam (NL) - Páramo Vegetation Research, Rabanal, Guerrero and Villa de Leyva paramo complex, Colombia. 3 records from ICN - Universidad Nacional de Colombia. 1 records from Field Museum of Natural History (Botany) Seed Plant Collection. 1 records from Colección del Herbario PSO de la Universidad de Nariño. 6 records from Instituto de Ciencias Naturales. 7 records from University of Amsterdam (NL) - Páramo Vegetation Research, Sumapaz-Bocagrande-Chisaca paramo complex, Colombia. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences